Pengaruh Penerapan Budaya Agile terhadap Keterlibatan dan Kinerja Karyawan PT. ASDP Indonesia Ferry (Persero) - Azan Yureski; Djoesept Harmat Tarigan (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research explores the impact of implementing Agile Culture on employee engagement and performance at PT ASDP Indonesia Ferry. Through a quantitative approach with a cross sectional survey design, data was collected from randomly selected employees. The analysis results show that Agile Culture has a significant influence on employee engagement and performance. Although the structural model showed low predictive power, the results of validity and reliability tests confirmed consistency in variable measurement. These findings confirm the great potential of Agile Culture in creating a responsive and productive work environment. The practical implication is that PT ASDP Indonesia Ferry can strengthen the implementation of Agile Culture through training and managerial support, while paying attention to factors that influence the predictive power of the model. Recommendations for further research include expanding the variables and sample population for a deeper understanding of the impact of Agile Culture. In conclusion, this research confirms that Agile Culture is an effective strategy in increasing employee engagement and performance, providing a foundation for the development of more effective HR strategies in the future.